Effects of Honey and Its Mechanisms of Action on the Development and Progression of Cancer - Erejuwa, Omotayo O.; Sulaiman, Siti A.; Ab Wahab, Mohd S. (MDPI, 2014)
Honey is a natural product known for its varied biological or pharmacological activities—ranging from anti-inflammatory, antioxidant, antibacterial, antihypertensive to hypoglycemic effects. This review article focuses on the role of honey in modulating the development and progression of tumors or cancers. It reviews available evidence (some of which is very recent) with regards to the antimetastatic, antiproliferative and anticancer effects of honey in various forms of cancer. These effects of honey have been thoroughly investigated in certain cancers such as breast, liver and colorectal cancer cell lines. In contrast, limited but promising data are available for other forms of cancers including prostate, bladder, endometrial, kidney, skin, cervical, oral and bone cancer cells. The article also underscores the various possible mechanisms by which honey may inhibit growth and proliferation of tumors or cancers. These include regulation of cell cycle, activation of mitochondrial pathway, induction of mitochondrial outer membrane permeabilization, induction of apoptosis, modulation of oxidative stress, amelioration of inflammation, modulation of insulin signaling and inhibition of angiogenesis. Honey is highly cytotoxic against tumor or cancer cells while it is non-cytotoxic to normal cells. The data indicate that honey can inhibit carcinogenesis by modulating the molecular processes of initiation, promotion, and progression stages. Thus, it may serve as a potential and promising anticancer agent which warrants further experimental and clinical studies.